Draft Genome Sequence of Lactobacillus salivarius SGL 03, a Novel Potential Probiotic Strain - Federici, Federica (Genome Announc, 2017)
In this work, we report the draft genome sequence of Lactobacillus salivarius SGL 03, a novel potential probiotic strain isolated from healthy infant stools. Antibiotic resistance analysis revealed the presence of a tetracycline resistance gene without elements potentially responsible for interspecific horizontal gene transfer.